DEVELOPING LANGUAGE COMPETENCE FOR TOURISM STUDENTS AND EMPLOYEES IN A BLENDED LEARNING LANGUAGE COURSE - Luka, Ineta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper presents the main findings of the second stage of Erasmus+ project „Key Skills for European Union Hotel Staff” (2014-2016) – the online course designed for A2/B1 level of language competence in 12 European languages and B2/C1 English language course to promote tourism students’ and employees’ language competence and raise their intercultural awareness. It analyses pedagogical, linguistic and field professional literature on course creation and presents the conducted evaluation research containing formative evaluation from three perspectives – provider (document review), recipient (a focus group interview with 14 learners) and wider community (a focus group interview with 7 hospitality industry managers and a survey of 21 language teachers from six countries) to identify the initiative’s consequences and opportunities for modification and improvement. The strengths and weaknesses of the course have been identified and suggestions on how the process could be made more efficient/effective for the organisation, the end users and the community have been provided.